Implementasi Metode SAW Pada Sistem Informasi Penyeleksian Peserta WUBI - Prasetya, Erawan; Alawiyah, Tuti; Ratningsih, Ratningsih (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - The BI Entrepreneurship Program is an annual Bank Indonesia Tasikmalaya Program with the aim of producing entrepreneurs who are quality and sustainable with a lot of knowledge from starting their respective product introductions to the Promotion Strategy. Participants who qualify for WUBI Selection will get funding from BI as the business capital of the participants. In the WUBI Participant Selection Implementation they still use a conventional system so that the WUBI Participant Selection Process takes a long time so it is not effective and efficient. Existing computerization systems that have not been computerized often cause difficulties in finding participant data because they still use files or documents. Solution to the problem in the selection of WUBI Participants, the authors designed the WUBI Participant Participation System based on the website and the Selection of Participants using the SAW Method using four criteria, namely Business Survey, Innovation, Creativity and Financial Managerial as supporting criteria for WUBI Participant Selection. Keywords: SAW, selection information system, WUBI